Cryptic local adaptation of the herbivorous ladybird beetle Henosepilachna pustulosa in the ability to use the thistle Cirsium boreale. Issue 1 (9th October 2021) - Fujiyama, Naoyuki; Kawasaki, Jun‐ichi; Katakura, Haruo
Abstract: Local adaptation to different host plants is important in the diversification of phytophagous insects. Thus far, much evidence of the local adaptation of insects with respect to host use at the physiological level has been gathered from systems involving less mobile insects and/or divergent hosts such as plants belonging to different families or genera. On the other hand, the prevalence of such local adaptation of insects with moderate or high dispersal ability to the intraspecific variation of herbaceous hosts is largely unknown. In the present study, we examined the occurrence and degree of local adaptation of the herbivorous ladybird beetle Henosepilachna pustulosa (Kôno) (Coleoptera: Coccinellidae) to its primary host, the thistle Cirsium boreale Kitam. (Asteraceae), through reciprocal laboratory experiments using beetles and thistles from three locations with a range of approximately 200 km. Concerning the larval developmental ability, obvious patterns of local adaptation to the thistles from respective natal locations were detected, at least in some combinations of beetle populations. Similar tendencies were detected concerning adult feeding acceptance, although the statistical support was somewhat obscure. Overall, our results indicate that the degree of local adaptation of insect species with moderate dispersal ability to conspecific herbaceous hosts is occasionally as strong as that involving less mobile insects and/or heterospecific hosts, indicating the potential of such cryptic local adaptation to promote ecological/genetic differentiation of phytophagous insect populations. Abstract : Local adaptation of a ladybird beetle (Coleoptera: Coccinellidae) to conspecific herbaceous hosts (Asteraceae) was examined through reciprocal laboratory experiments. Based on larval development, obvious local adaptation to hosts from natal locations was detected at least in some combinations. Similar tendencies were also detected based on adult feeding acceptance. Our results indicate that the degree of local adaptation of insects with moderate dispersal ability to conspecific herbaceous hosts is occasionally as strong as that involving less mobile insects and/or heterospecific hosts.